Opposing the European Union or looking for more reforms: different facets of Euroscepticism in Estonia - Viljar Veebel (Romanian Journal of European Affairs, 2017)
Although public support for EU membership is strong in Estonia, some Eurosceptic views are also expressed. Most of the agents and groups with Eurosceptic views could be classified as soft Eurosceptics, including some politicians and public figures. However, from time to time Euro-populist ideas combined with hard Euroscepticism have emerged too, mostly among the politicians, but their overall influence in society is rather modest today. Nevertheless, as regards the economic perspective, the Eurosceptic views and arguments in Estonia are often based on pure economic rationality, which could in principle refer to the origins of “Euro-pragmatism” in Estonia. Thus, a “positive program” is needed where the focus is not on the statements like “we do not need Eurosceptics”, but on the question of how Eurosceptics could contribute to a more sustainable European Union.